Deal or no deal: Will the US Inflation Reduction Act (IRA) push Carbon Capture and Storage (CCS) and Carbon Dioxide Removal (CDR) technologies over the line? - Andrew Goddard (The Oxford Institute for Energy Studies, 2023)
The Inflation Reduction Act (IRA) provides unprecedented support for climate and the clean energy transition in the US. This study evaluates relevant measures within the IRA, the 45Q tax credit in particular, and examines its likely effectiveness in mobilizing private finance for carbon capture, utilization and storage (CCUS) and carbon dioxide removal (CDR) in areas needed to reach net-zero. The study adapts and leverages the concept of 'blended finance' as one of few theoretical and prescriptive frameworks available to examine the role of public impact financing in hard-to-finance areas. The study's objective is to evaluate the IRA's impact to the CCUS/CDR investment landscape in the US and concludes that hard-to-mitigate risks are likely to persist.
Keywords: 330; 45Q; Carbon Capture and Storage; Carbon dioxide removal; Carbon finance; CCS; CO2 utilization; Direct Air Capture; Industrial Decarbonization; Inflation Reduction Act; net-zero